SEISMOTECTONICS OF THE SOUTHERN MARMARA REGION, NW TURKEY - Yalçın, H.; Kürçer, A.; Utkucu, M.; Gülen, L. (Bulletin of the Geological Society of Greece, 2016)
The Southern Marmara Region is an active deformation area, which is a transition zone between the strike-slip tectonics manifested by the North Anatolian Fault System and the N-S extensional regime of the Aegean Region. We have reviewed tectonic and geological structure of the region, based on seismological studies. We have obtained a total of 37 earthquake moment tensor solutions between 1953 and 2015. In addition, stress tensor analysis has been carried out using 37 earthquake moment tensor solutions. Also long term seismicity were investigated and a,b, Mc values were calculated and mapped. Moment tensor solutions indicate that the source of these earthquakes are mostly NE-trending dextral strike-slip faults and some of them are E-W trending dip-slip normal faults. The stress tensor analysis shows that the direction of the regional compressive stress is NW-SE. The temporal and spatial distrubution of the large earthquakes (1944, 1953, 1964) indicate that the ruptures unilaterally propagate from SW to NE. The 1855 earthquake had been occurred to the east of Manyas Lake. The elapsed time (160 year) and regional stress transfer suggest that the segments to the east of Manyas Lake form a probable seismic gap and this area has a high earthquake risk.